A real-time de-noising method applied for transient and weak biomolecular interaction analysis in surface plasmon resonance biosensing. (9th February 2016) - Zhan, Shuyue; Shi, Chunfei; Ou, Huichao; Song, Hong; Wang, Xiaoping
Abstract: Surface plasmon resonance (SPR) biosensing technology will likely become a type of label-free technology for transient and weak biomolecular interaction analysis (BIA); however, it needs some improvement with regard to high-speed and high-resolution measurement. We studied a type of real-time de-noising (RD) data processing method for SPR sensorgrams based on moving average; it can immediately distinguish ultra-weak signals during the process of experiment, and can display a low-noise sensorgram in real time. A flow injection analysis experiment and a CM5 sensorchip affinity experiment are designed to evaluate the characteristics of the RD method. High noise suppression ability and low signal distortion risks of the RD method have been proved. The RD method does not significantly distort signals of the sensorgram in the molecular affinity experiment, and K D values of the RD method essentially coincide with those of the raw sensorgram with a higher signal-to-noise ratio (SNR). Meanwhile, by the RD method denoising the sensorgram with an ultralow SNR that is closer to the condition of the transient and weak molecular interactions, the kinetic constant can be more accurately analyzed, whereas it cannot be realized for the raw sensorgram. The crucial function and significance of the RD method are primarily embodied in the measurement limit of SPR sensing.